Development of optimization method of the repair work taking into account the risk indicators - Лыфарь, Владимир Алексеевич; Сафонова, Светлана Александровна; Иванов, Виталий Геннадьевич (Technology audit and production reserves, 2015)
The methods of data collection and processing residual resource determination, planning repair work by optimizing the decision based on the criteria of acceptable risk level of reliability and performance of the equipment are developed. Optimization of planning the repair work is achieved as a result of Risk Based Inspection using information technology of risk assessment. The proposed technology allows to combine the study of cause-and-effect relationships of processes based on fault tree analysis (FTA) and modeling the possible consequences of failure. As a result, using the methods of sorting the coefficients of the value and the maximum allowable risk parameters provide the sequence and chronology of the necessary recovery procedures. The aim of article is to achieve repair regime depend on condition. This can significantly reduce the cost of repairs.